Integrative neuromuscular training and injury prevention in youth athletes. Part I: Identifying risk factors - Fort-Vanmeerhaeghe, A.; Romero-Rodriguez, D.; Montalvo, A. M.; Kiefer, A. W.; Lloyd, R. S.; Myer, G. D. (Strength and Conditioning Journal, 2016)
Part i of this review describes the most important neuromuscular sports injury risk factors in youth athletes: muscle fatigue, altered timing and magnitude of muscle activation, strength deficits, predominance of frontal plane control strategies, neuromuscular imbalances between limbs, inadequate muscle stiffness, deficits in postural stability, altered proprioception, and feed-forward control. The second part of this review provides a flexible approach to integrative neuromuscular training with the goal to improve injury resilience and to enhance sport and motor skill performance.